Analysis of Problems in Learners' Collaboration Ability towards Chemistry Learning: Systematic Literature Review - Linda, Desma; Menno, Ayu Windy Malisa; Simanjuntak, Yanni Irma Waty (Postgraduate, University of Mataram, 2024)
Collaboration skills involving active participation, flexibility, responsibility, and appreciation are very important in chemistry learning, especially since chemistry contains abstract and complex concepts that are often difficult for students to understand. This research aims to describe the literature review on student collaboration skills in the context of chemistry learning. The method used in this research is Systematic Literature Review (SLR), with articles taken from the Scopus database and supported by Publish or Perish (PoP) in the range of 2013-2023. This research focuses on problems and solutions related to student collaboration skills, especially in the context of chemistry learning. The results showed that the difficulties faced by students in understanding chemistry materials can lead to low student collaboration skills. The problems of students' collaboration skills include the lack of teachers' ability to choose the right learning model/approach/method as well as physical limitations (practicum experience, limited access to materials and equipment), and lack of interactivity in chemistry lessons causing low student collaboration. Therefore, appropriate strategies, approaches, and learning models as well as supporting infrastructure are needed in learning chemistry. One of the appropriate learning models/approaches to improve student collaboration is Discovery Learning, and cooperative learning models of TGT, PBL, and PjBL types. In addition, this also needs to be supported by interesting teaching materials in order to help improve students' collaboration skills in learning.